Expression analysis of beta-secretase 1 (BACE1) enzyme in peripheral blood of patients with Alzheimer\'s disease - Alireza Vakilian; Javad Masoumi; Saeid Mirzaee; Hossein Khorramdelazad (Babol University of Medical Sciences, 2019)
Background: Recent evidence has indicated that beta-secretase 1 (BACE1) is involved in the production of amyloid beta (Aβ) in patients affected with Alzheimer's disease (AD). Therefore; the purpose of this study was to measure mRNA and plasma levels of BACE1 in AD patients, as an early diagnosis biomarker for such individuals. Methods: A total number of thirty AD patients and thirty normal subjects as controls were recriuted in the present study. Plasma levels of BACE1 were then examined via enzyme-linked immunosorbent assay (ELISA) and also mRNA expression of BACE1 in total blood was measured using real-time PCR technique. Results: The findings revealed a significant difference in gene expression of BACE1 in the peripheral blood of AD patients compared with that in controls (p<0.0001). Additionally, elevated plasma levels of BACE1 were found in AD patients compared with those in normal subjects (p<0.01). Statistical analyses also demonstrated no correlation between expression (mRNA and protein) of BACE1 in both AD patients and controls and age or the results of Mini-Mental State Examination (MMSE) scale (p>0.05). Conclusion: Given the importance of early diagnosis of AD patients, it was suggested that the measurement of plasma levels and also mRNA expression of BACE1 might be a valuable blood-based biomarker used in preference to other invasive diagnostic methods such as cerebrospinal fluid (CSF) analysis.